2020
DOI: 10.3390/molecules25030636
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Synthesis, Antioxidant Properties, and Self-Assembly of Carotenoid–Flavonoid Conjugates

Abstract: Flavonoids and carotenoids possess beneficial physiological effects, such as high antioxidant capacity, anticarcinogenic, immunomodulatory, and anti-inflammatory properties, as well as protective effects against UV light. The covalent coupling of hydrophobic carotenoids with hydrophilic flavonoids, such as daidzein and chrysin, was achieved, resulting in new amphipathic structures. 7-Azidohexyl ethers of daidzein and chrysin were prepared in five steps, and their azide-alkyne [4 + 2] cycloaddition with pentyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Aronia has been reported to be rich in anthocyanins such as cyanidin-3-O-glucoside, cyanidin-3-O-xyloside, cyanidin-3-O-galactoside, and cyanidin-3-O-arabinoside [45]. Flavonoid glycosides are a form of sugar bound to flavonoids, which improve the physicochemical properties of hydrophobic flavonoids, including solubility, intra-and intercellular transport, chemical stability, and biological half-life [46]. Flavonoid glycosides, which are known to have higher antioxidant activity than flavonoid aglycone in vitro, are considered to be more suitable as food packaging materials [47].…”
Section: Antioxidant Activity Of Aronia Powders and Bioelastomersmentioning
confidence: 99%
“…Aronia has been reported to be rich in anthocyanins such as cyanidin-3-O-glucoside, cyanidin-3-O-xyloside, cyanidin-3-O-galactoside, and cyanidin-3-O-arabinoside [45]. Flavonoid glycosides are a form of sugar bound to flavonoids, which improve the physicochemical properties of hydrophobic flavonoids, including solubility, intra-and intercellular transport, chemical stability, and biological half-life [46]. Flavonoid glycosides, which are known to have higher antioxidant activity than flavonoid aglycone in vitro, are considered to be more suitable as food packaging materials [47].…”
Section: Antioxidant Activity Of Aronia Powders and Bioelastomersmentioning
confidence: 99%
“…circular dichroism is needed for confirmation [ 41 , 42 ]. We have some recent experience of such behaviour of carotenoid-flavonoid conjugates [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the antioxidant activity of the flavonoids and carotenoids, Linzembold et al (2020) reported the conjugation of daidzein and chrysin with carotenoids ( Figure 27 ). These hybrids were synthesized by Click Chemistry reaction in the presence of bis-triphenylphosphano-copper (I)-butyrate complex and DCM, giving rise to compounds 76a – 76b and 77a – 77b with 40–88% yield [ 116 ]. The trolox-equivalent antioxidant capacity (TEAC) of the synthetic conjugates was investigated towards ABTS •+ radical cation.…”
Section: Other Activitiesmentioning
confidence: 99%